Lichen Amyloidosis Resembles A Picture Chronic Lichen Simplex in A Woman with Hyperpigmented Skin Lesions Area Lower Legs - Jilly Selena Pradipta (Indonesian Journal of Global Health Research, 2024)
Lichen Amyloidosis (LA) and Lichen Simplex Chronicus (LSC) are two skin conditions that are often confused in clinical diagnosis because of their similar clinical manifestations. Objective: This study aims to determine the picture of Lichen Amyloidosis Resembling Lichen Simplex Chronicus in Women with Hyperpigmented Skin Lesions in the Lower Leg Area. This study used a qualitative method with a case study approach on participants who met the inclusion and exclusion criteria in women with hyperpigmented skin lesions in the lower leg area. The population and samples used were patients who met the inclusion and exclusion criteria as many as 3 people. patients were interviewed, observed and given medical treatment then evaluated for changes that occurred. The results of this study found a case of a 37-year-old woman with hyperpigmented skin lesions on both lower legs, diagnosed as LSC. Further examination showed results in accordance with LA. The main symptoms experienced by the patient were severe itching that interfered with daily activities, especially when the patient was emotional or stressed. The patient was treated using a combination of dermatotherapy and psychotherapy to reduce itching and prevent recurrence. Diagnostic challenges are often encountered in the management of patients with complex skin conditions, as is the importance of accurate histopathology in establishing a correct diagnosis.